The End of Salvation History - Hinze, Bradford E. (Horizons, 1991)
The debate about salvation history brings to the surface a variety of issues, problems, and proposals that can be designated with some justice postmodern. In an effort to explore these contested issues, I offer a composite portrait of the meaning and uses of the concept of salvation history, drawing attention to its importance for recent Roman Catholic theology. I then review the various kinds of criticism leveled against salvation history models in an attempt to show that Peter Hodgson's contention is warranted: that is, the concept salvation history is problematic both as a category for interpreting the scriptural witness and as a pivotal category for fundamental and systematic theology. Thus, postmodernity, understood in broad terms, should mean the end of salvation history. The final section will explore how the legitimate concerns that generated interest in salvation history models can be recast in light of these broader postmodern approaches.